Correction: A high energy density asymmetric supercapacitor utilizing a nickel phosphate/graphene foam composite as the cathode and carbonized iron cations adsorbed onto polyaniline as the anode. Issue 25 (17th April 2018) - Mirghni, A. A.; Madito, M. J.; Oyedotun, K. O.; Masikhwa, T. M.; Ndiaye, N. M.; Ray, Sekhar C.; Manyala, N.
Abstract : Correction for 'A high energy density asymmetric supercapacitor utilizing a nickel phosphate/graphene foam composite as the cathode and carbonized iron cations adsorbed onto polyaniline as the anode' by A. A. Mirghni et al., RSC Adv., 2018, 8, 11608–11621.